Determining the protocol requirements of in-home cat food digestibility testing - Bos, E.; Hendriks, W. H.; Beerda, B.; Bosch, G. (Frontiers in Veterinary Science, 2023)
In-home cat food digestibility testing has the potential to yield data that are highly representative of the pet population for which the food is intended. However, no standardized and validated in-home digestibility test protocols are currently available. Such protocols for in-home testing should address key factors that explain variation in cat food digestibility values and here we investigated the required period of adaptation, fecal collection and sample sizes. Thirty privately-owned indoor housed cats of various breeds (20♀10♂, 5.9±3.9 yr, 4.5±1.3 kg) received a relatively low and high digestible complete dry extruded food with the marker titanium (Ti) dioxide. Foods were given in a cross-over design of 2 periods of 8 consecutive days each. Owners collected feces daily for the determination of daily fecal Ti concentrations and digestibility of dry matter, crude protein, crude fat, and gross energy. Data originating from 26 cats were analyzed as mixed models and broken line regressions to investigate the required adaptation and fecal collection period. Bootstrap sampling was used to assess the impact of increasing the number of fecal collection days and sample size on the precision of the digestibility estimates. Feces were collected on 347 out of 416 study days (16 days/cat; 26 cats), implying the necessity for multiple collection days to account for cats not defecating every day. Cats showed stable fecal marker concentrations from day 2 onwards when fed the low digestible food and from 3 onwards when fed the high digestible food. Digestibility values were stable from day 1, 2 or 3 onwards, depending on the test food and nutrient. Increasing the number of fecal collection days from 1 to 6 days did not result in more precise digestibility estimates, whereas increasing the number of animals from 5 to 25 cats did. For future in-home digestibility tests of cat food, the findings support a minimum of 2 adaptation days and 3 fecal collection days. Appropriate sample sizes depend on the test food, the nutrient of interest, and the acceptable margin of error. The findings of this study support the protocol development for future in-home digestibility testing of cat foods.